Comparing Robert Frostsâ€™ Poems; Stopping by Woods on a Snowy Evening and The Sound of Trees - Riru, Kusmarlin; Nurindah, Nurindah; Sapan, Yulius Tandi (Journal of Teaching of English, 2021)
This study aims to find out the similarities and the differences of Robert Frostsâ€™ poems â€œStopping by Woods on a Snowy Eveningâ€ and â€œThe Sound of Treesâ€ in terms of imagery and figurative language. The design of the study used a qualitative design with a descriptive semantic approach. Data analysis used descriptive and content analysis techniques. This study found that the poem â€œStopping by Woods on a Snowingâ€ contains two types of imagery namely visual and auditory and three types of figurative language namely metaphor, personification, and hyperbole. There are three types of imagery namely visual imagery, auditory imagery, and organic imagery, and four types of figurative languages namely Â Â metaphor, simile, personification, and irony in the poem â€œThe Sound of Treesâ€. Furthermore, the two poems have similarities and differences in terms of imagery and figurative language. Both of them have visual imagery and auditory imagery as well as metaphor and personification. Besides having similarities and differences in terms of imagery and figurative language, the two poems also have similarities and differences in terms of imagery characteristics. What the two poems have in common is that they both have the speaker I as a man, natural theme, and setting of the place, which is at home, even though the marker word for the imagery is different. Meanwhile, the difference lies in the listener, and the setting of the situation namely the listener of the poem â€œStopping by Woods on a Snowy Eveningâ€ which is the little horse and woods with a snow and the darkest evening setting. Meanwhile, the listener of the poem â€œThe Sound of Treesâ€ is the trees with a white cloud situation setting.